Electrical conductivity and alcohol sensing studies on polythiophene tin oxide nanocomposites - Husain, Ahmad (H. : ĐHQGHN, 2020)
Conducting polymer-based sensors have short response time at room temperature besides their good electrical conductivity. However, the poor electrical conductivity retention at a higher temperature and the failing reproducibility of sensors which are based on conducting polymers are an area of concern. To this end, we are reporting the preparation of polythiophene (PTh) and polythiophene/Tin oxide (PTh/ SnO2) nanocomposites by an in-situ chemical oxidative polymerisation. The as-prepared materials were characterized by FTIR, SEM, UV-vis absorbance spectroscopy, TEM and XRD techniques. PTh/SnO2-3 (i.e. PTh/SnO2 nanocomposite containing 15% SnO2 nanoparticles) showed the highest DC electrical conductivity (9.82 10 3 S,cm 1) in addition to a maximal stability as a function of DC electrical conductivity retention under accelerated isothermal and cyclic ageing conditions. We utilized PTh/SnO2-3 to fabricate a novel pellet-shaped sensor for the selective detection of some of the higher alcohols, such as butan-1-ol (1 alcohol), butan-2-ol (2 alcohol), and 2-methyl propanol (3 alcohol) at room temperature. PTh/SnO2-3 exhibited the highest response in terms of variation in DC electrical conductivity and maximal reproducibility for butan-1-ol. Finally, the sensing mechanism was explained by the adsorption edesorption process of alcohol vapours on the large surface area of the PTh/SnO2 nanocomposites where electronic interactions between the lone pairs of electrons of alcohol molecules with the polarons of PTh cause the change in the DC electrical conductivity.